2022
DOI: 10.1152/ajplung.00299.2021
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine signature clusters as a tool to compare changes associated with tobacco product use in upper and lower airway samples

Abstract: Inhalation exposure to cigarette smoke and e-cigarette aerosol is known to alter the respiratory immune system, particularly cytokine signaling. In assessments of health impacts of tobacco product use, cytokines are often measured using a variety of sample types, from serum to airway mucosa. However, it is currently unclear whether and how well cytokine levels from different sample types and the airway locations they represent are correlated, making comparing studies that utilize differing sample types challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…These include a cluster with IP-10, IFNγ, IL-2, IL-4 (r = 0.39, gray, Figure 2), and a cluster with IL-5, Eotaxin, and TNFβ (r = 0.26, green, Figure 2). Differences in clusters of mediators may identify patterns among immune mediators with interacting correlated functions that are not evident when evaluating individual mediators alone, a finding that has previously been reported in other airway biomarker studies of smokers (Payton et al, 2022). These clusters have some biological plausibility, as increases in included mediators have been reported with cigarette smoke exposure in multiple studies.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…These include a cluster with IP-10, IFNγ, IL-2, IL-4 (r = 0.39, gray, Figure 2), and a cluster with IL-5, Eotaxin, and TNFβ (r = 0.26, green, Figure 2). Differences in clusters of mediators may identify patterns among immune mediators with interacting correlated functions that are not evident when evaluating individual mediators alone, a finding that has previously been reported in other airway biomarker studies of smokers (Payton et al, 2022). These clusters have some biological plausibility, as increases in included mediators have been reported with cigarette smoke exposure in multiple studies.…”
Section: Discussionmentioning
confidence: 66%
“…This exploratory study further suggests that the nasal passage may be an ideal target for biomarker detection. It has already been demonstrated that serum biomarkers are often not the best representative source for information on respiratory immune status; rather, airway samples, even from sources such as the nose, are better correlates for lower airway than circulating blood (Payton et al, 2022 ). In the future, nasosorption may be a feasible method to evaluate respiratory biomarkers of disease or exposure in the clinical environment with further validation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further investigate the impact of each condensate (plastic or cardboard) and burn conditions (control, smoldering, or flaming) on cytokine and gene expression profiles after exposure, principal component analysis (PCA) was performed to understand if these sample conditions yield similar expression profiles at an aggregate level ignoring the donor-to-donor variations, similar to our previous study. 36 This subset of sample conditions was prioritized to enhance the resulting visualizations while focusing on conditions of high importance. PCA is an unsupervised machine learning technique that seeks to compress the variance from an original data set into the fewest number of principal components.…”
Section: Statistical Analysis Of Cytokine and Gene Expressionmentioning
confidence: 99%
“…One unsupervised ML algorithm, k-means, groups observations into the optimal number of clusters with each observation belonging to the clusters with the closest mean (Ecosystem, 2018). As an example, an inhalation toxicology study carried out by our group evaluated cytokine signatures derived from multiple biological samples that commonly inform respiratory responses, including nasal lavage fluid, nasal epithelial lining fluid, sputum, and circulating serum, to determine if cytokine levels differed based on these sampling locations (Payton et al, 2022). K-means grouped cytokines into clusters within each respiratory tract region, separately.…”
Section: Discovering Patterns In Highdimensional Data Using Unsupervi...mentioning
confidence: 99%